MENINGKATKAN LOYALITAS PELANGGAN DALAM MENGHADAPI PERSAINGAN RITEL (Studi Pada Toko Warakas) - Hafif, Andi (Master of Management Diponegoro University, 2014)
Competition in the retail business is growing rapidly Semarang, where there are currentlymany emerging minimarket in the entire city of Semarang. The level of competition in theretail world market is very tight and had too many players who are involved with very largecapital, to face the market competition is too tight the need for the concept of different strategieswith other competitors who have very large capital. Right strategy to enter the market withdifferent marketing concept is the social business strategy, and grew to involve the community,where companies try to gain an advantage, but also to solve social problems by using businessmethods.This research will discuss about improving customer loyalty through customer retention tosupport competitiveness of prices, incentives and community stakeholders the role of socialcommunities. The sampling technique used in this study is purposive sampling method.Respondents who used as much as 115 respondents are mothers decision makers in thecommunity entered by Warakas.The data analysis technique used is stuctural equation model (SEM) of the software AMOS21. Results of SEM analysis for the full model has met the criteria for Goodness of Fit - FullModel is a chi square of 97.016; probability of 0.139; CMIN / DF amounted to 1,169; GFI by0904; TLI was 0.970; CFI of 0.976; RMSEA of 0.038. Thus it can be said that this model isfeasible to use.The test results of the four hypotheses, proving the existence of a single hypothesis is rejected.Based on this research can be concluded that there are two factors that significantly affectcustomer retention is the price competitiveness of the social and community stakeholders.The price competitiveness of the factors proved to have the strongest influence on customerretention than the social community stakeholders while not proven community incentives affecÂ customer retention.